The Determinant of Policy Termination Post-Leadership Succession in Indonesia Context - Iswahyudi, Fajar; Hadna, Agus Heruanto; Darwin, Muhadjir; Kutanegara, Pande Made (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
Theoretically, termination of policy is due to policy effectiveness. However, in leadership succession, there is a responsibility to acknowledge voters' preferences. Thus, post-leadership succession policy termination can be caused by the policies' effectiveness and voters' policy preferences. This research tries to explain how policy effectiveness and voter preferences become determinants of post-leadership succession policy termination. The analysis was carried out using the multi-stream framework (MSF) developed by Kingdon. The case study chosen was the termination of the River Concretization Policy (RCP) in Jakarta, Indonesia. The research method used is qualitative. This research finds that RCP termination's determinants are effectivity of the program and voter policy preference. This research reaffirms the importance of policy effectiveness and voter policy preference as a foundation for policy termination in post-leadership succession.